Dynamic and kinematic characteristics of unsteady motion of a water-in-oil emulsion droplet in collision with a solid heated wall under conditions of convective heat transfer - Semyonova A. E. Aleksandra Evgenjevna; Khomutov N. A. Nikita Andreevich; Misyura S. Ya. Sergey Yakovlevich; Piskunov M. V. Maksim Vladimirovich (2022, 2022)
Title screen